Literatur Review Hubungan Perubahan Iklim dengan Transmisi Malaria di Wilayah Tropis - Nurasmi Fuji; Vindia Wathaniah; Radhiah Zakaria (Pelantar Press, 2026)
Malaria remains a major public health problem in tropical regions. Climate change leads to increased temperature, humidity, and rainfall, which affect the ecology of Anopheles mosquitoes as the primary vector of malaria. These conditions may expand transmission areas and prolong vector survival. The purpose of this study To review the influence of climate change on the spread and incidence of malaria in tropical regions based on recent studies published in 2024–2025. This study is a literature review by searching scientific articles through PubMed, Scopus, and nationally indexed journals (SINTA). Articles that met the inclusion criteria were analyzed descriptively based on temperature, humidity, and rainfall variables related to malaria occurrence. The review found that an increase in temperature (25–32°C) and humidity (70–85%) accelerates parasite development and extends mosquito lifespan. Excessive rainfall increases the number of breeding habitats. The combination of these factors elevates the risk of malaria transmission in tropical regions. Conclusions is Climate change significantly influences malaria transmission through environmental alterations and vector behavior changes. Adaptive control strategies and climate-based surveillance systems are required to prevent future increases in malaria incidence